Differences in the signaling pathways of α(1A)- and α(1B)-adrenoceptors are related to different endosomal targeting. - Vanessa Segura; Miguel Pérez-Aso; Fermí Montó; Elena Carceller; María Antonia Noguera; John Pediani; Graeme Milligan; Ian Christie McGrath; Pilar D'Ocon (PLoS ONE, 2013)
AIMS: To compare the constitutive and agonist-dependent endosomal trafficking of α(1A)- and α(1B)-adrenoceptors (ARs) and to establish if the internalization pattern determines the signaling pathways of each subtype. METHODS: Using CypHer5 technology and VSV-G epitope tagged α(1A)- and α(1B)-ARs stably and transiently expressed in HEK 293 cells, we analyzed by confocal microscopy the constitutive and agonist-induced internalization of each subtype, and the temporal relationship between agonist induced internalization and the increase in intracellular calcium (determined by FLUO-3 flouorescence), or the phosphorylation of ERK1/2 and p38 MAP kinases (determined by Western blot). RESULTS AND CONCLUSIONS: Constitutive as well as agonist-induced trafficking of α(1A) and α(1B) ARs maintain two different endosomal pools of receptors: one located close to the plasma membrane and the other deeper into the cytosol. Each subtype exhibited specific characteristics of internalization and distribution between these pools that determines their signaling pathways: α(1A)-ARs, when located in the plasma membrane, signal through calcium and ERK1/2 pathways but, when translocated to deeper endosomes, through a mechanism sensitive to β-arrestin and concanavalin A, continue signaling through ERK1/2 and also activate the p38 pathway. α(1B)-ARs signal through calcium and ERK1/2 only when located in the membrane and the signals disappear after endocytosis and by disruption of the membrane lipid rafts by methyl-β-cyclodextrin.